2010
DOI: 10.3324/haematol.2009.020073
|View full text |Cite
|
Sign up to set email alerts
|

Voriconazole for secondary prophylaxis of invasive fungal infections in allogeneic stem cell transplant recipients: results of the VOSIFI study

Abstract: A complete list of the members of the VOSIFI Study Group is provided in the Appendix. BackgroundRecurrence of prior invasive fungal infection (relapse rate of 30-50%) limits the success of stem cell transplantation. Secondary prophylaxis could reduce disease burden and improve survival. Design and MethodsA prospective, open-label, multicenter trial was conducted evaluating voriconazole (4 mg/kg/12 h intravenously or 200 mg/12 h orally) as secondary antifungal prophylaxis in allogeneic stem cell transplant reci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(73 citation statements)
references
References 33 publications
3
66
1
3
Order By: Relevance
“…Of note, 93% of our patients received a second generation triazole as secondary prophylaxis. Our data are in agreement with those of a recent prospective open-labeled study 9 that also demonstrated a low-relapsed IMI rate after HSCT (7%), as well as previous retrospective studies 5,7 in the era of secondary prophylaxis with second-generation azoles.…”
supporting
confidence: 83%
“…Of note, 93% of our patients received a second generation triazole as secondary prophylaxis. Our data are in agreement with those of a recent prospective open-labeled study 9 that also demonstrated a low-relapsed IMI rate after HSCT (7%), as well as previous retrospective studies 5,7 in the era of secondary prophylaxis with second-generation azoles.…”
supporting
confidence: 83%
“…[3][4][5] More recent publications clearly demonstrate the feasibility of allo-HSCT in patients with a history of IA. 1,[6][7][8] In the present study, the Infectious Diseases and Acute Leukemia Working Parties of The European Society for Blood and Marrow Transplantation (EBMT) had the aim to analyze the long-term outcome of patients with acute leukemia undergoing allo-HSCT according to the presence-or absence of pre-existing IA.…”
Section: Introductionmentioning
confidence: 99%
“…W profilaktyce wtórnej u dorosłych proponuje się obecnie worikonazol. W badaniu prospektywnym obejmującym 45 chorych, reaktywacja IFI wystąpiła u 7% chorych [68]. Doniesienia dotyczące profilaktyki wtórnej IA u dzieci są nieliczne.…”
Section: Terapia Skojarzonaunclassified